Analisis Pengelolaan Pendapatan Pajak Kendaraan Bermotor Berbasis Akuntabilitas Keuangan di Kabupaten Lombok Utara - Sukma, Leni Aprilia; Nabila, Tialurra Della (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the management of Motor Vehicle Tax (PKB) revenue based on financial accountability in North Lombok Regency. The research employed a descriptive qualitative approach, utilizing in-depth interviews, observation, and documentation as data collection techniques. The results indicate that PKB management in North Lombok Regency has been generally effective, with annual revenue realization consistently exceeding the set targets. However, the application of financial accountability principles, such as financial reporting transparency and public participation, still faces challenges, particularly limited information access and low fiscal literacy among the public. Supporting factors for accountability implementation include the use of digital systems like e-Samsat and inter-agency synergy, while obstacles involve geographical barriers, low community income, and limited digital literacy. The study concludes that enhancing financial accountability in PKB management can strengthen public trust in local governments and support the optimization of regional revenue.